Sequence Alignment between vWF and Peptides Inhibiting the vWF-collagen Interaction Does not Result in the Identification of a Collagen-binding Site in vWF - Vanhoorelbeke, K.; van der Plas, R. M.; Vandecasteele, G.; Vauterin, S.; Huizinga, E. G.; Sixma, J. J.; Deckmyn, H. (Thrombosis and Haemostasis, 2000)
We previously found that two peptides (N- and Q-peptide) selected by phage display for binding to an anti-vWF antibody, were able to inhibit vWF-binding to collagen (1). The sequence of those peptides could be aligned with the sequence in vWF at position 1129-1136 just outside the A3-domain. As the peptides represent an epitope or mimotope of vWF for binding to collagen we next wanted to study whether the alignment resulted in the identification of a new collagen binding site in vWF. We mutated the 1129-1136 VWTLPDQC sequence in vWF to VATAPAAC. Expressing this mutant vWF (7.8-vWF) in a fur-BHK cell line resulted in well processed 7.8-vWF containing a normal distribution of molecular weight multimers. However, binding studies of this mutant vWF to rat tail, human and calf skin collagens type I, to human collagen types III and VI, revealed no decrease in vWF-binding to any of these collagens. Thus, although the N-and Q-peptides did inhibit the vWF-collagen interaction, the resulting alignment with the vWF sequence did not identify a collagen binding site, pointing out that alignments (although with a high percentage of identity) do not always result in identification of binding epitopes. However, suprisingly removal of the A3-domain or changing the vWF sequence at position 1129-1136 resulted in an increase of vWF-binding to human collagen type VI and to rat tail collagen type I, implying that these changes result in a different conformation of vWF with an increased binding to these collagens as a consequence.
Keywords: vWF-collagen binding; mimotope; mutagenesis; platelets